A system for road pavement Life Cycle Cost (LCC) analysis - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2019)
Research Management Centre of International Islamic University Manalaysia selected IIUM inventors to present Invention Poster in the competition of Invention & Innovation Awards 2019, Malaysia Technology Expo (MTE 2019) at Putra World Trade Centre from 21st to 23rd February 2019.